The funeral kit mortuary practices in the archaeological record - Baker, Jill L., 1964- (Left Coast Press, 2012)
"Studies of mortuary archaeology tend to focus on difference--how the researcher can identify age, gender, status, and ethnicity from the contents of a burial. Jill L. Baker's innovative approach begins from the opposite point: how can you recognize the commonalities of a culture from the "funeral kit" that occurs in all burials, irrespective of status differences? And what do those commonalities have to say about the world view and religious beliefs of that culture? Baker begins with the Middle and Late Bronze Age tombs in the southern Levant, then expands her scope in ever widening circles to create a general model of the funeral kit of use to archaeologists in a wide variety of cultures and settings. The volume will be of equal value to specialists in Near Eastern archaeology and those who study mortuary remains in ancient cultures worldwide"--